AN APPROACH FOR PRESERVING OTTOMAN CULTURAL HERITAGE UNDER THREAT IN YEMEN: A CASE STUDY " THE OLD CITY OF SANA'A" - Yahya Abdullah Alamri; Betül EKİMCİ; Mehmet İNCEOĞLU (Journal of Islamic Architecture, 2022)
Cultural heritage is one of the human development aspects throughout the historical ages. Yemen is one of the wealthiest regions with cultural heritages in the Middle East, due to its important geographical location linking India, China, Africa, and the Mediterranean countries. Sana'a developed through successive Islamic eras, one of the most important of them was during Ottoman period. During their presence in Yemen, Ottomans were interested in constructing different types of buildings and bringing about a great civilizational and architectural renaissance in various regions of Yemen, especially in the city of Sana'a. However, cultural heritage in Sana'a was badly damaged during the Yemeni conflict, including Ottoman heritage. This study proposes an approach for preserving the building's cultural heritage under threat. This approach was based on the European Standard (EN 16096:2012 (E)), Conservation of cultural property - Condition survey and report of building’s cultural heritage. The methodology used will help preserve the cultural heritage in Sana'a by assessing the damage caused by the war in Sana'a, and appropriate proposals were made. This study considered a group of Ottoman structures in the old city of Sana'a as a case study. It shows the war-affected historical sites in all Yemeni cities. During the period of Ottoman rule in Yemen, various facilities were built in most regions of Yemen, most of which were concentrated in the old city of Sana'a. Ottoman establishments were counted in the old city of Sana'a, where there were twenty-eight of them, twenty-one installations still in existence, and seven destroyed and no longer existing.